2019
DOI: 10.3389/fimmu.2019.02129
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's Tyrosine Kinase Inhibition Attenuates the Cardiac Dysfunction Caused by Cecal Ligation and Puncture in Mice

Abstract: Sepsis is one of the most prevalent diseases in the world. The development of cardiac dysfunction in sepsis results in an increase of mortality. It is known that Bruton's tyrosine kinase (BTK) plays a role in toll-like receptor signaling and NLRP3 inflammasome activation, two key components in the pathophysiology of sepsis and sepsis-associated cardiac dysfunction. In this study we investigated whether pharmacological inhibition of BTK (ibrutinib 30 mg/kg and acalabrutinib 3 mg/kg) attenuates sepsis associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 34 publications
5
35
1
Order By: Relevance
“…They were subjected to a 12 h light and dark cycle with a temperature maintained at 19–23°C. Group sizes for each experiment were calculated following power calculations based on previous studies ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…They were subjected to a 12 h light and dark cycle with a temperature maintained at 19–23°C. Group sizes for each experiment were calculated following power calculations based on previous studies ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cecal ligation and puncture (CLP) was performed in 10 week-old male CBA (wild type) or Xid mice as previously described ( 14 , 22 ). Mice were randomly assigned to undergo CLP or sham-operated surgery, the surgeon was blinded to the genotype of the mouse.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NLRP3 is expressed in several cell types, as innate immunity, endothelial, haematopoietic, lung epithelial, kidney, and cardiac cells (Ratajczak & Kucia, 2020). We and others have previously demonstrated that NLRP3 inflammasome over-activation contributes to the pathogenesis of cardio-metabolic disorders (Mastrocola, Collino, et al, 2016;O'Riordan et al, 2019;Zuurbier et al, 2019), whereas NLRP3 deficiency results in reduced systemic inflammation, along with a decreased immune cell activation and improved insulin resistance (Grant & Dixit, 2013;Vandanmagsar et al, 2011). The NLRP3 inflammasome is also a crucial player in immune defence of the host against many pathogens, including viruses (Z.…”
Section: The Nlrp3 Inflammasome and Its Role In Viral Infectionmentioning
confidence: 99%